Antidiabetic, Antioxidants and Antibacterial Activities of Lactic Acid Bacteria (LAB) from Masin (Fermented Sauce from Sumbawa, West Nusa Tenggara, Indonesia) - Manguntungi, Baso; Vanggy, Leggina Rezzy; Fidien, Khadijah Alliya Fidien; Saputri, Dinar Suksmayu Saputri; Mustopa, Apon Zaenal; Ekawati, Nurlaili; Nurfatwa, Maritsa; Prastyowati, Anika; Irawan, Shasmita (Annales Bogorienses, 2020)
The study aimed to determine the effectiveness of metabolites from Lactic Acid Bacteria (LAB) derived Masin (fermented sauce from Sumbawa) as antioxidant, antidiabetic, and antibacterial compounds. The LAB isolates were isolated from various strains of Staphylococcus piscifermentan which consisted of Staphylococcus piscifermentans strain CIP103958 (code: 2), strain BULST54 (code: 17), strain SK03 (code: 11), strain ATCC 51136 (code: 34), strain PCM 2409 (code: 28) and strain PU-87 (code: 5). The Metabolites of LAB were analyzed by the bioprospecting test to indicate antidiabetic, antioxidant and antibacterial activities. The isolate (Code: 5) at 500 ug/ml showed the most effective antioxidant activity up to 71%. The isolate (code: 28), at 300 ug/ml revealed to have the most antidiabetic activity up to 43 %. The isolate (code: 2) showed moderate antibacterial activity with the inhibition zone of 5.59 mm. The results of the antidiabetic, antioxidant and antibacterial activity showed that the secondary metabolites produced by LAB from the Masin have broad activities as an antidiabetic, antioxidant and antibacterial.